Desempenho produtivo, digestibilidade e características ruminais de cabras Saanen recebendo rações com casca do grão de soja em substituição ao milho - Zambom, Maximiliane Alavarse (2006)
The work aimed to evaluate digestive parameters, milk production and quality of Saanen goats fed rations with soybean hulls (SBH) as a cracked corn replacement. The treatments were consisted of replacement levels of cracked corn for SBH (0%SBH, 50%SBH and 100%SBH), with the rations presenting 14.89% of CP and 2.57 Mcal of ME/kg DMI as mean values. The study of digestive parameters and ruminal fermentation was accomplished by using three Saanen goats, confined and first-kidding, allocated in a 3X3 Latin square design. Digestibility, productive performance and milk quality were also studied, during lactation, prepartum period and following lactation, which was divided in two parts: one at the beginning of lactation, before its peak of production, and the other after the peak. Eighteen Saanen goats were used (lactation and prepartum) and 14 ones at the following lactation, all of them housed in individual pens, with daily control of intake and milk production. Feces were sampled for the determination of dry matter and nutrient digestibility, and ruminal liquid was collected to determine ruminal parameters. Milk samples were collected for physical-chemical analyses and fatty acid profile. For all the evaluated phases, treatments did not affect live weight, nor the production and the physical-chemical quality of milk. Starch intake (kg/day) was greater for 0%SBH treatment. For dry matter intake, it was verified difference among treatments only in prepartum period. Neutral detergent fiber intake (NDFI) was greater for 100%SBH treatment, in the phases: lactation, prepartum and beginning of following lactation. Related to dry matter digestibility, differences were verified among treatments in the beginning of lactation, and for NDF digestibility, it was observed a larger percentage for 100%SBH, in lactation, in prepartum period and beginning of lactation. Ration with 100%SBH provided higher concentration of ruminal acetate, greater acetate:propionate ratio and lower ruminal propionate and butyrate contents. Treatments did not affect ruminal N-NH3 and pH. Milk fatty acid profile was changed by the treatments in all evaluated phases. Soybean hulls can replace cracked corn in rations for Saanen goats during prepartum period and lactation without any changes in digestive process, production and milk quality.